DYNAMICS, SCOPE AND STRUCTURE OF EXTERNAL TRADE OF THE REPUBLIC OF SERBIA - Kisin, Jovana; Ignjatović, Jelena; Mašović, Azemina (Poslovna ekonomija, 2022)
The COVID-19 pandemic has changed global economic perspectives and led to a turning point in economic trends around the world, as well ass in the Republic of Serbia. With a detailed analysis of key figures of external trade of goods, the main aim of this paper is to appraise the position and results of the Republic of Serbia in the field of foreign trade exchange, as one of the most important indicators of economic activity. The methodology covered in the paper includes qualitative research techniques, such as analysis, comparative analysis, and synthesis. The first part of the paper deals with the trend of external trade in the past three decades, with special reference to the effect of the crisis caused by the COVID-19 pandemic. The second thematic unit analyzes the structure of the Republic of Serbia’s foreign trade, according to the economic purpose of goods and the classification of activities. The focus of the third part is the territorial distribution of foreign trade of the Republic of Serbia by main economic and geographical zones, ie countries of purpose and origin. Finally, concluding remarks are given. We found that the Republic of Serbia has many possibilities to improve external trade, which should primarily focus on increasing exports, in quantitative terms, but at the same time not neglect to raise the quality and value of our export products.